Clinical efficacy of a traditional Japanese (kampo) medicine for burning mouth syndrome. Issue 2 (October 2016) - Sakata, Ken‐ichiro; Yamazaki, Yutaka; Ohga, Noritaka; Sato, Jun; Asaka, Takuya; Yoshikawa, Kazuhito; Nakazawa, Seitaro; Sato, Chiharu; Nakamura, Yusuke; Kitagawa, Yoshimasa
Abstract: Aim: At Hokkaido University Hospital, selective serotonin re‐uptake inhibitors (SSRI) or serotonin and norepinephrine re‐uptake inhibitors (SNRI) are the first‐line medications for burning mouth syndrome (BMS). Occasionally, when standard SSRI/SNRI are deemed inappropriate because of certain side‐effects, treatment incompatibility, age concerns, or doctor discretion, a kampo medicine called rikkosan can be used. The purpose of this study was to evaluate the effectiveness of rikkosan for BMS. Methods: This retrospective study included 48 patients (four men, 44 women; mean age, 70 years) who were diagnosed with BMS in the present department between 2006 and 2014. Only patients who received rikkosan (7.5 g/day) for >4 weeks were included. Patients who were taking other medicines for BMS were excluded. Pain was assessed using a visual analog scale. Results: Improvement was seen in 54% of patients (26/48). Conclusion: Rikkosan is an effective alternative treatment for BMS.